A Neuro Linguistic Programming"s modelling process for the development of and guidance to congregations: An adaptive ministry - Bester, Johan (HTS teologiese studies, 2019)
Several congregations in the workspace of the Netherdutch Reformed Church of Africa are losing viability and sustainability. This can be attributed to various factors, the most prominent being isolation. Isolation is defined here as the inability of some congregations to move away from maintenance and an inward focus towards making necessary adjustments on the way to a dimension of missional focus. While commitment and enthusiasm are present in the work of all congregations, some find it difficult to adapt their established ideas and in some cases obsolete customs and traditions. Other congregations have made the necessary adjustments by defining themselves as missional. In congregations where constructive change occurs, the focus moves to undertake congregational ministries. The congregation not only gains insight into their own situation but also becomes aware of God’s calling for that specific congregation within a specific context. The focus shifts from their own situation and needs to the needs and challenges of the context surrounding the specific congregation. A consequence of this change in focus is that the whole ministry of the congregation adjusts accordingly. These congregations discover their own unique spirituality and begin to ask: For whom do we exist? The article is based on a PhD thesis, where Osmer’s four questions of practical theology were brought into the conversation with the modelling process of neuro-linguistic programming, in an attempt to sojourn with congregations towards a contextual missional focus. This research was undertaken to expand Osmer’s four questions of practical theology by using the modelling process of neuro-linguistic programming so that congregations may succeed in making the necessary adjustments.